2019
DOI: 10.1088/1674-4527/19/3/34
|View full text |Cite
|
Sign up to set email alerts
|

Database of molecular masers and variable stars

Abstract: We present the database of maser sources in H 2 O, OH and SiO lines that can be used to identify and study variable stars at evolved stages. Detecting the maser emission in H 2 O, OH and SiO molecules toward infrared-excess objects is one of the methods of identification long-period variables (LPVs, including Miras and Semi-Regular), because these stars exhibit maser activity in their circumstellar shells. Our sample contains 1803 known LPV objects. 46% of these stars (832 objects) manifest maser emission in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In addition, Class I masers require lower densities and temperatures than Class II masers (Menten 2012), making them more numerous. Specifically for the J −1 → (J − 1) 0 − E series with J = 4 and 5, their intensities were predicted to be on the order of 50 mJy in the case of NGC 253 (Sobolev 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Class I masers require lower densities and temperatures than Class II masers (Menten 2012), making them more numerous. Specifically for the J −1 → (J − 1) 0 − E series with J = 4 and 5, their intensities were predicted to be on the order of 50 mJy in the case of NGC 253 (Sobolev 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Three out of five objects were detected successfully in both frequencies, although the SNR in the weaker signals was ~2σ. The characteristics of the spectra and the obtained velocities were compared with results from scientific publications [12]- [14] and maser.db [15]. The obtained results were verified and considered correct.…”
Section: Resultsmentioning
confidence: 67%
“…Class I methanol masers were detected not only in our Galaxy but in several external galaxies. More than 25 years ago, Sobolev (1993) suggested that search for extragalactic methanol masers should be most promising in the starburst galaxies in the 36.2 GHz class I methanol transition. After that, there were several unsuccessful searches for methanol masers in galaxies (Ellingsen et al 1994;Phillips et al 1998;Darling et al 2003), but these searches were focused on the class II transition at 6.7 GHz, probably inspired by the detection of 6.7 GHz methanol maser in LMC (Sinclair et al 1992).…”
Section: Introductionmentioning
confidence: 99%